(untitled) (World Bulletin of Social Sciences, 2025)
During the years of independence, strong medical protection of the population became the main, priority direction of state policy. The only goal pursued by all the reforms implemented in the Republic of Uzbekistan over the past years was to create a normal medical culture for citizens, to provide continuous economic support to the underprivileged and needy part of the population.